Motor neurone disease: towards better care. - Norris, F H (1985)
Even in the most severe forms of motor neurone disease--progressive bulbar palsy and amyotrophic lateral sclerosis--the symptoms and disabilities from progressive paralysis may be relieved in many patients by various symptomatic treatments. Quality of life may be improved even in the terminal stage, when narcotic administration should be considered. The physician's proper role is to offer and carefully supervise these treatments, not withhold them. Home care is recommended even for the most severely paralysed, though hospice care may be a good alternative. The underlying principle--to alleviate symptoms--applies to the management of all progressive incurable diseases.